التيارات الوافدة بين التطبيق والتوافق دراسة تحليلية لعمارة اللاذقية الوافدة مابين الحربين نحو صياغة عمارة توافقية - محمود سلمان; صيداوي وليد; بدر رنا (Latakia University Journal -Engineering Sciences Series, 2019)
لطالما تشكلت صيغة المجتمعات وتطورت متأثرة بمجموعة كبيرة من المتغيرات (الاجتماعية , الاقتصادية , والروحية , والقيمية،..) والتي كان أي تغيّر في تأثيرها ينعكس على تغيّر المجتمع وتطوره . من هنا كان تأثر البنى المعمارية في المجتمعات المستعمرة بعمارة الوافد الجديد أمراً واقعاً إما من خلال التحاكي والتأثير أو عدمه في أنماط العمارة . فهل استطاعت هذه العمارة المستوردة والمفروضة أن تعكس واقع مجتمعها الجديد ؟ سؤال طرحه الباحث ليحقق أهداف بحثه في تتبع مقدار التوافقية من عدمها لمفردات العمارة الوافدة مع المجتمع، ومحاولة صياغة نموذج يعظم التوافق ويقلص التنافر بين مفردات العمارة الوافدة (بعد التصرف بها) والعمارة المعاصرة ( إن جاز التعبير ) في إطار النظام الحالي للمدينة القديمة . Formation of societies has always been affected by many variables (social, economic, and of value ); in turn, any change in their influence is reflected in society’s change and development. Thus, the effect of architectural structures on societies colonized by the new incoming architecture is a matter of course either through immitation or otherwise of architectural trends. So has this imported or imposed architecture reflected the reality of its new society? A question is asked to achieve the aims of this research by following the quantity of harmony or disharmony of the incoming architectural vocabularies infiltrating society, and an attempt to form a model capable of maximizing harmony and minimizing disharmony between incoming architectural vocabularies and contemporary ones in the framework of current architectural system of the ancient city.